Mastectomy under Local Anesthesia in Locally Advanced Breast Cancer in an Unfit Patient (Bangladesh Journal of Medical Science, 2022)
Breast cancer is the most common cancer and leading cause of death in women. Mostly it is present in old age with advanced stage. Mastectomy under generalanesthesia is the treatment of choice. But as old age is associated with some co-morbidity which increase the operative risk and contraindication for operation. Here we describe a case of 50-year female came to Outpatient Department of AbbasiShaheedHospital with complaint of left breast lump for 1 year and dry cough for 2 weeks. On examination there was a large fungating mass on left breast with palpable left axillary lymph nodes.Trucut biopsy shows invasive ductal carcinoma grade II. Mastectomy was planned under general anesthesia but due to some respiratory problems general anesthesia fitness was not obtained. So in view of patient condition, toilet mastectomy under local anesthesia was done successfully. Local anesthesia is safe and effective method in patients who have substantial risk for general anesthesia. Successful surgeries under local anesthesia have already been reported and it should be preferred when it is necessary.Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 745-748